2013
DOI: 10.1517/17425255.2013.813018
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of ilaprazole for gastro-esophageal reflux treatment

Abstract: Different studies show that ilaprazole, a benzimidazole derivative, has an extended plasma half-life in comparison with all other approved PPIs. In addition, ilaprazole metabolism is not significantly influenced by CYP2C19, compared to the available PPIs. Furthermore, the pharmacological characteristics of ilaprazole confer theoretical advantages that are expected to translate into an improved acid control, particularly at night time. However, studies comparing the clinical pharmacokinetics and pharmacodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…[28][29][30] Accordingly, ilaprazole is expected to have a longer duration of action and less NAB compared to other PPIs. 31,32 But we found that GERD symptoms, 24-hour mean gastric pH, nocturnal mean gastric pH, frequency and duration of NAB, were comparable between the ilaprazole and omeprazole groups. The only significant difference was occurrence of lesser number of NAB episodes in the ilaprazole group.…”
Section: Discussionmentioning
confidence: 70%
“…[28][29][30] Accordingly, ilaprazole is expected to have a longer duration of action and less NAB compared to other PPIs. 31,32 But we found that GERD symptoms, 24-hour mean gastric pH, nocturnal mean gastric pH, frequency and duration of NAB, were comparable between the ilaprazole and omeprazole groups. The only significant difference was occurrence of lesser number of NAB episodes in the ilaprazole group.…”
Section: Discussionmentioning
confidence: 70%
“…10 Of note, the favourable pharmacokinetic pattern of ilaprazole, relying mainly in a lack of influence by CYP 2 C 19 genetic polymorphism and a prolonged elimination half-life, is expected to impact positively, in terms of lower variability and long lasting acid inhibition, on the inhibition of gastric acid secretion. 11 In this survey, the commonly encountered acid peptic disorders observed were GERD followed by peptic ulcer disease. Commonly reported symptoms of APD are heartburn, regurgitation, abdominal discomfort, nausea, sleep disturbances.…”
Section: Discussionmentioning
confidence: 90%
“…This is mainly due to a high clarithromycin-resistance rate; however, it is also possible that the cause is a CYP2C19 polymorphism [20]. Ilaprazole is primarily metabolized by CYP3A4 and is not influenced by CYP2C19 genetic polymorphisms [21]. In addition, ilaprazole has a long half-life, which leads to a longer period of gastric acid suppression and higher ulcer healing rates compared with other PPIs.…”
Section: Discussionmentioning
confidence: 99%